Optimalisasi Pemberian Ammonium Sulfat terhadap Produksi Nata De Banana Skin - Evy Rossi; Usman Pato; S.R. Damanik (Jurnal Sagu, 2008)
The effects of ammonium sulphate on physical properties of bacterial cellulose-Nata de banana skin produced by Acetobacter xylinum had been studied. The pupose of this study was to find out the optimum concentration of ammonium sulphate that can be used to produce maximum Nata de banana skin. A completely randomized design was used in this research and the treatments were concentrations of ammonium sulphate; A1 (0,4% per vol), A2 (0,8% per vol), and A3(1,2% per vol). The result showed that various concentrations of ammonium sulphate significantly affected  the tital bacteria population, but did not provide different results for thickness, weight, moisture and yield.